If only Arvanitika had an admirative mood! Between evidentiality and counterfactuality - Liosis, Nikos (Zeitschrift für Balkanologie, 2010)
In this paper I examine mainly from a morphosyntactic, semantic and typological perspective the presence in Hydra Arvanitika of certain forms historically derived from an inverted past perfect which are formally equivalent to today’s Albanian imperfect admirative. These inherited forms are not based any more on the stem of the truncated participle as is the case for all Albanian admirative types, but rather on the stem of the optative mood as a result of reanalysis. They also seem to have lost their nonconfirmative meaning and to convey modal distinctions in a narrower semantic frame: they appear exclusively in counterfactual constructions (conditionals, wishes) with past reference, thus partially taking over the semantic role of the optative and rendering the system of conditionals and wishes hypercharacterized in comparison with both Standard Modern Greek and Albanian.